The Influence Of Transformational Leadership On Job Satisfaction Mediated Work Engagement Of Civil Servants in The Cooperative, SMEs, Industry and Trade Office of Bungo Regency - Novriansyah, Yudhi; R, Misra Yeni; Roni, Khairun A; Harahab, Delila Fitri (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The purpose of this research is to analyze the influence of Transformational Leadership on Job Satisfaction Mediated by Work Engagement of Civil Servants in the Cooperative, SMEs, Industry, and Trade Office of Bungo Regency. This research using Explanatory study method by conducting quantitative data analysis on 33 respondents and data processing using Partial Least Square (PLS) 4.0. Result of this study show that Transformational Leadership positively influences Job Satisfaction, and Transformational Leadership influences Employee Work Engagement. Meanwhile, indirectly, Transformational Leadership has a positive and significant effect on Job Satisfaction mediated by the Work Engagement of Civil Servants in the Cooperatives, SMEs, Industry, and Trade Office of Bungo Regency.